An in-vitro antimicrobial effect of 405 nm laser diode combined with chlorophylls of Alfalfa (Medicago sativa L.) on Enterococcus faecalis - Suryani Dyah Astuti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: Enterococcus faecalis (E. faecalis) is a bacterium commonly detected in the root canals of teeth with post-treatment apical periodontitis or advanced marginal periodontitis. It has the ability to live in an extreme environment and survive as an organism with its virulence factor possibly contributing to the pathogenesis of post-treatment apical and marginal periodontitis. Photodynamic therapy (PDT) is an urgently required alternative method of improving therapy effectiveness. Photodynamic therapy combined with conventional endodontic treatment decreases the number of antibioticresistant bacteria and biofilms. Chlorophyll is one of the photosensitizers added to enhance the absorption of light in photodynamic therapy. Purpose: The purpose of this study was to determine the antimicrobial effect of the combination of photodynamic laser therapy and Alfalfa chlorophyll in E. faecalis. Methods: In vitro study using E. faecalis distributed between negative control (C-) and positive control (C+), treatment groups using various energy doses of a 405 nm diode laser (2.5, 5, 7.5, 10, 12.5, 15, 17.5, 20 J/cm2) with (G1) and without alfalfa chlorophyll as organic photosensitizer (G2). The suspension was inoculated on Tryptocase Soy Agar (TSA) and incubated at 37° C for 24 hours. The number of colonyforming units per milliliter (CFU/ml) was determined. The results were analyzed by ANOVA with p value ≤0.05. Results: A 405 nm irradiating laser with or without a photosensitizer can decrease E. faecalis viability percentage through the administering of various energy doses. The highest decrease (42%) was obtained in the group without a photosensitizer using 20 J/cm2, while 10 J/cm2 in the group with a photosensitizer proved the most effective dose (25%). Conclusion: The results of this study showed a decrease in the viability of E. faecalis exposed to a 405 nm (40 mW) laser. An irradiating process using a 405 nm laser without a photosensitizer (Alfalfa chlorophyll) resulted in the highest percentage decrease (42%) in E. faecalis bacterial viability.